2022
DOI: 10.1101/2022.10.01.509820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comprehensive view of cell-type-specific temporal dynamics in human and mouse brains

Abstract: Progenitor cells play fundamental roles in preserving optimal organismal functions under normal, aging, and disease conditions. However, progenitor cells are incompletely characterized, especially in the brain, partly because conventional methods are restricted by inadequate throughput and resolution for deciphering cell-type-specific proliferation and differentiation dynamics in vivo. Here, we developed TrackerSci, a new technique that combines in vivo labeling of newborn cells with single-cell combinatorial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Then we identified potential marker genes for pericytes using Monocle. 47 We filtered the significant pericyte marker genes (q-value <0.05) to a subset of seven genes (Table 1), by applying the following criteria: a high expression in pericytes (>700 TPM), but a low expression in any other cell types (<400 TPM). We further excluded two genes from this list, because the second highest expression was in smooth muscle cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then we identified potential marker genes for pericytes using Monocle. 47 We filtered the significant pericyte marker genes (q-value <0.05) to a subset of seven genes (Table 1), by applying the following criteria: a high expression in pericytes (>700 TPM), but a low expression in any other cell types (<400 TPM). We further excluded two genes from this list, because the second highest expression was in smooth muscle cells.…”
Section: Resultsmentioning
confidence: 99%
“…After clustering the vascular cells from the human brain samples, we identified subclusters correlating with pericytes, smooth muscle cells, endothelial cells and perivascular fibroblasts (Figure 1C). Then we identified potential marker genes for pericytes using Monocle 47 . We filtered the significant pericyte marker genes (q‐value <0.05) to a subset of seven genes (Table 1), by applying the following criteria: a high expression in pericytes (>700 TPM), but a low expression in any other cell types (<400 TPM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies uncovered the prevalence of CREs in plants, highlighting their dynamic nature throughout evolution and their involvement in regulating gene expression via distinct chromatin pathways [3][4][5][6][7][8] . Across diverse cell types, gene expression is intricately regulated by multipl 9 e distinct CREs, each exerting control within specific cell or tissue types or during particular developmental stages and environmental cues [10][11][12] . Several studies have identified CREs functioning in a cell-type-specific manner within various plant species 9,[13][14][15][16][17][18][19] .…”
mentioning
confidence: 99%
“…Prior studies highlighted the dynamic nature of CREs throughout evolution and their involvement in regulating gene expression via distinct chromatin pathways [4][5][6][7][8][9] . Across diverse cell types, gene expression is intricately regulated by multiple distinct CREs, each exerting control within specific cell or tissue type or particular developmental stage and environmental cue [10][11][12] . Environmental sensing and adaptation, in plants, relies heavily upon epidermal cells 13 .…”
mentioning
confidence: 99%